2004
DOI: 10.1021/la049519p
|View full text |Cite
|
Sign up to set email alerts
|

The Outermost Atomic Layer of Thin Films of Fluorinated Polymethacrylates

Abstract: In this paper, we investigate the surface properties of a series of copolymers of perfluoroalkyl methacrylate (CH2 = C(CH3)COOCH2CnF(2n + 1), n = 1, 6, or 10) and methyl methacrylate (MMA) and of blends of perfluorooctyl-end-capped poly(methyl methacrylate) (PMMA) and pure PMMA. The introduction of perfluoroalkyl groups significantly lowers the polymer surface energy as determined by the acid-base approach. X-ray photoelectron spectroscopy (XPS) confirms a higher fluorine concentration in the surface region (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 42 publications
3
43
1
Order By: Relevance
“…It is well-known that the molecular weights of the perfluoro acrylic copolymers synthesized in CO 2 medium were higher than the copolymers obtained in polar organic solvents [6,10,39]. DeSimone et al reported that the copolymer molecular weight of FOA with MMA in scCO 2 were more than 270,000 g/mol [10], whereas other researchers reported that the solution copolymerization of perfluoro alkyl methacrylate with MMA in MEK [39] and in BuOAc [6] resulted in much lower molecular weights which were in the range of 20,000-25,000 g/mol.…”
Section: Copolymer Characterizationmentioning
confidence: 96%
See 2 more Smart Citations
“…It is well-known that the molecular weights of the perfluoro acrylic copolymers synthesized in CO 2 medium were higher than the copolymers obtained in polar organic solvents [6,10,39]. DeSimone et al reported that the copolymer molecular weight of FOA with MMA in scCO 2 were more than 270,000 g/mol [10], whereas other researchers reported that the solution copolymerization of perfluoro alkyl methacrylate with MMA in MEK [39] and in BuOAc [6] resulted in much lower molecular weights which were in the range of 20,000-25,000 g/mol.…”
Section: Copolymer Characterizationmentioning
confidence: 96%
“…In general, fluoropolymers are categorized as main-chain and side-chain fluoropolymers, and most of the side-chain fluoropolymers are synthesized from the polymerization reaction of the fluorinated methacrylate monomers [4]. The introduction of the pendant fluorinated groups through the acrylic monomers which have perfluoroalkyl side groups, decreases the surface tension of the obtained copolymer films [5,6]. Fluoro methacrylate (FMA) copolymers have been used increasingly in a wide range of applications including surface coatings for textile, paper and leather industries, biomaterials, microelectronics and antifouling [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for surface applications focusing on hydrophobicity, copolymers of fluorinated and conventional monomers can be effectively employed since the fluorinated groups segregate at the solid-air interface to decrease surface energy. 1,[7][8][9] In addition, self-assembly of fluorinated block copolymers in various environments has been successfully utilized to fabricate nano-structures having a wide range of morphologies which have found applications in emerging technologies such as nano-optics, nano-electronics and nanobiotechnology. 10,11 Low surface energy of the fluorinated polymers is commonly utilized in the area of superhydrophobicity, a subject that became popular when the naturally micro-textured surface of the non-wettable lotus leaves was discovered.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the chain shapes or the conformations of polymers in solutions could affect the structures and properties of the polymers in bulk [22,23]. The influence of the preparation methods on the surface properties of fluorinated polymers has been reported in several publications [21,[24][25][26][27][28][29] and it was found that various surface structures can be obtained by controlling film-formation conditions such as the solvent species and preparation methods. When methyl methacrylate (MMA) and 2-perfluorooctylethyl methacrylate (FMA) block copolymer (PMMA-b-PFMA) film was prepared from its micelle solution with PMMA block as micelle corona and PFMA block as 0021-9797/$ -see front matter Ó 2010 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%